Knowledge, health seeking behavior and barriers for treatment of reproductive tract infections among married women of reproductive age in Delhi - Doley, Preety; Yadav, Geeta; Gupta, Monika; Muralidhar, Sumathi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Reproductive tract infections including sexually transmitted infections are an important public health problem among women of reproductive age group in developing countries. The perceptions or taboos related to RTIs act as an obstacle for seeking treatment ultimately leading to complications. The aim of the study was to assess the knowledge, health seeking behavior and barriers for treatment of reproductive tract infections among married women of reproductive age in Delhi. Methods: A community based cross-sectional study was undertaken in an urban field practice area of department of Community Medicine of VMMC and Safdarjung Hospital, New Delhi from November 2017 to April 2019. Sample size of 270 was collected using predesigned and pre- tested questionnaire by systematic random sampling. Results: Mere 16.6% of the women knew about symptoms of RTI/STIs. Out of 81 women having RTI/STI in past 3 months 30% did not seek treatment and out of 70% who took treatment for RTI, 30% did not complete treatment. Majority of the women who sought treatment preferred government hospital. The main barrier for seeking treatment was embarrassment, not considering it as an important health problem, lack of time. Conclusions: The overall knowledge about symptoms, mode of spread of RTIs/STIs was very poor among the study participants. Women seeking treatment are not completing it. Thus, there is need to emphasize on spreading knowledge about symptoms, mode of spread, need for treatment and its completion and clearing barriers related to RTI/STI among women.